Occupational performance of the Primary School children with special needs - Voo, Siew Ching (2015)
Children's occupations are self-care, play, social participation and education. Their performance can be impaired by physical, developmental, sensory, attention and or learning challenges. In developed countries school-based therapy services are being provided for the school children with special needs. The evidence for these services in Malaysia is timely to be explored. This study aimed to identify the occupational performance levels in the study population. This exploratory cross sectional study included 121 primary school students from integrated special education program. Motor-Free Visual Perceptual Test 3rd.ed (MVPT), Beery-Buktenica Developmental Test of Visual Motor Integration 5th .ed (Beery-VMI), Test of Gross Motor Development - 2 (TGMD-2), Test of Hand Writing Skills-Revised (THS-R) and School Function Assessment (SFA) were carried out to assess occupational performance. Children with intellectual disability, autism, attention deficit hyperactive disorder, Down syndrome, speech impairment, visual impairment, hearing impairment and specific learning disorder were included. Results showed that 69.5% of the students scored low average to very low in MVPT-3; 69.4% scored below average to very low in Beery-VMI; 73% were below age level raw score in TGMD-2; 72.8% were below average in THS-R and 81% were below criterion cut off in participation in school function. Significant relationship was found between gross motor skill, VMI and visual perception to school function and VMI and visual perception to hand writing skill. School-based therapy and other rehabilitation services in the school system are recommended. Early intervention program to improve motor skill, visual perception and visual motor integration is important for the preschool children with special needs.